2020
DOI: 10.1371/journal.pgen.1008543
|View full text |Cite
|
Sign up to set email alerts
|

The Lid/KDM5 histone demethylase complex activates a critical effector of the oocyte-to-zygote transition

Abstract: Following fertilization of a mature oocyte, the formation of a diploid zygote involves a series of coordinated cellular events that ends with the first embryonic mitosis. In animals, this complex developmental transition is almost entirely controlled by maternal gene products. How such a crucial transcriptional program is established during oogenesis remains poorly understood. Here, we have performed an shRNA-based genetic screen in Drosophila to identify genes required to form a diploid zygote. We found that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…key regulators, such as GNU, LID and DHD, exhibit protein level patterns that are consistent with their functions during the transition (Torres-Campana et al 2020;Kronja et al 2014a;Petrova et al 2018). Similar to these proteins, many other proteins show protein level patterns suggestive of developmental control (Kronja et al 2014a).…”
Section: Discussionmentioning
confidence: 70%
“…key regulators, such as GNU, LID and DHD, exhibit protein level patterns that are consistent with their functions during the transition (Torres-Campana et al 2020;Kronja et al 2014a;Petrova et al 2018). Similar to these proteins, many other proteins show protein level patterns suggestive of developmental control (Kronja et al 2014a).…”
Section: Discussionmentioning
confidence: 70%
“…We previously showed that H3K4me3, a histone modification associated with active transcription, is enriched at the dhd promoter and that this mark is lost in lid KD ovaries [5](FigS2-A). Further exploiting published ChIP-seq datasets, we surprisingly found that dhd lies within a ∼5kbp mini-domain featuring two types of repressive histone modifications: H3K27me3 and H3K9me3 [24, 25].…”
Section: Resultsmentioning
confidence: 99%
“…Understanding their function therefore requires identifying biologically relevant situations where disrupting these effectors impacts transcription in a critical and specific manner. We previously described one of such cases, where perturbation of the histone demethylase Lid/KDM5 or the histone deacetylase scaffold Sin3A in Drosophila ovaries dramatically abrogated the expression of the essential maternal gene deadhead (dhd) [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Dhd plays crucial roles in the oocyte-to-embryo transition, where it reduces and modulates the activity of ribosomal and RNA-binding proteins, as well as that of the histone demethylase NO66 (Petrova et al, 2018). Recently, the transcriptional regulation of Dhd has been reported to be modulated by the lysinespecific demethylase 5 (KDM5), a potent chromatin remodeler during female gametogenesis (Torres-Campana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%